Classification, nosology and diagnostics of Ehlers-Danlos syndrome - Ben C J Hamel (Journal of Biomedicine and Translational Research, 2019)
Ehlers-Danlos syndrome (EDS) comprises a group of heritable connective tissue disorders which has as cardinal features varying degrees of skin hyperextensibility, joint hypermobility, easy bruising and skin fragility. The 2017 New York nosology distinguishes 13 types of EDS, which all, except hypermobile EDS, have a known molecular basis. Hypermobile EDS is recognized as a common and often disabling disorder, incorporating benign joint hypermobility syndrome. EDS needs to be differentiated from other connective tissue disorders, in particular Marfan syndrome, Loeys-Dietz syndrome and cutis laxa. The frequent types of EDS can be diagnosed after careful history taking and clinical examination, but for definite diagnosis molecular confirmation is needed in all types. Management for EDS patients preferably is provided by multidisciplinary teams in expertise centres. After diagnosing EDS genetic counselling is an essential part of the management of patients and their family.